Cinta, Keperawanan, dan Rasa Malu: Analisis Feminis Interseksional terhadap Kekerasan Dalam Pacaran (KDP) - Melinda Siahaan; Reymond Pandapotan Sianturi; Agustina Lumbantobing; Rolima Rajagukguk; Cahaya Julita Gea (Asosiasi Teolog Indonesia, 2023)
This paper discusses the phenomenon of dating violence, or kekerasan dalam pacaran (KDP). Although a perpetrator evinces threats upon personal safety, victims tend to defend and rationalize a perpetrator's negative behaviour by considering KDP a unique form of love, care, and affection. This stance perpetuates KDP on the one hand, while it hinders advocacy efforts for victims on the other. The authors conducted a study of the experiences of KDP among eleven female undergraduate students in North Tapanuli Regency. Through its use of an intersectional feminist perspective proposed by Kimberlé Crenshaw, this paper finds that cultural, religious, gendered, and economic factors play a pivotal role in a victim’s stance to maintain KDP relations. Such victoms of KDP become trapped in overlapping injustices caused by the KDP perpetrator, cultures of discriminatory gender relations within a patriarchal society, an errant theological interpretation of love and forgiveness, and even poverty. This article offers three points for a theological reconstruction: a (corrective) theology of love and forgiveness, of imago Dei, and of shame and accountability.